FRI0293 Characterization and risk estimate of cancer in primary sjÖgren syndrome: analysis in 1300 patients. (15th June 2017) - Brito-Zerόn, P; Kostov, B; Fraile, G; Caravia-Durán, D; Maure, B; Rascόn, F-J; Zamora, M; Casanovas, A; Lopez-Dupla, M; Ripoll, M; Pinilla, B; Fonseca, E; et al.
Abstract : Objectives: To characterize the risk of solid and hematological cancer in a large, well-characterized cohort of patients with primary Sjögren syndrome (SjS). Methods: The GEAS-SS multicenter registry is a network of Spanish reference centers with specific clinical experience in the management of SjS patients. By January 2016, we had analyzed the development of cancer in 1300 consecutive patients fulfilling the 2002 SjS classification criteria. Multivariate Cox proportional-hazards regression analysis allowed adjustment for age at diagnosis, gender and the statistically-significant baseline variables associated with cancer in the univariate analysis. The sex- and age-specific incidence rates (SIR) of cancer were estimated from 2012 Spanish mortality data modeling, using a set of age-, sex- and site-specific incidence:mortality ratios. Results: After a mean follow-up of 91 months (9922.3 person-years), 127 (9.8%) patients developed 133 cancers. The most frequent type of cancer was B-cell lymphoma (34% of cancers, including 27 MALT and 19 non-MALT B-cell lymphomas). Systemic activity at diagnosis of primary SjS correlated with the risk of hematological neoplasia (HR 1.06, p<0.001). Positive cryoglobulins at SjS diagnosis were associated with a high risk of either B-cell or non-B-cell lymphoma subtypes. Patients with cytopenias had a high risk of non-MALT B-cell and non-B-cell cancer, while those with low C3 levels had a high risk of MALT lymphomas and those with monoclonal gammopathy and low C4 levels had a high risk of non-MALT B-cell lymphomas. The estimated SIR for solid cancer was 1.13 (95% CI 0.88–1.46) and 11.02 (95% CI 8.35–14.54) for hematological cancer. SIRs for specific cancers were 36.17 (95% CI 25.44–51.43) for multiple myeloma and immunoproliferative diseases, 19.41 (95% CI 7.29–51.72) for Hodgkin lymphoma, 6.04 (95% CI 3.43–10.64) for other non-Hodgkin lymphomas, 5.17 (95% CI 1.94–13.79) for thyroid cancer, 4.81 (95% CI 1.81–12.83) for cancers of the lip and oral cavity and 2.53 (95% CI 1.05–6.07) for stomach cancer. Conclusions: One third of cancers developed by patients with primary SjS are B-cell lymphomas. The prognostic factors identified at SjS diagnosis differed according to the subtype of B-cell lymphoma developed. Primary SjS is also associated with an enhanced risk of development of some types of non-hematological cancers (thyroid, oral cavity and stomach). Disclosure of Interest: None declared